2020
DOI: 10.1007/s00464-020-07846-4
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized controlled trial on comparison of standard CO2 pressure pneumoperitoneum insufflator versus AirSeal®

Abstract: Background AirSeal® is a valve-free insufflation system that enables a stable pneumoperitoneum with continuous smoke evacuation and CO 2 recirculation during laparoscopic surgery. Comparative evidence on the use of AirSeal® and standard CO 2 insufflator in laparoscopic general surgery procedures is scarce. The aim of this study was to compare surgical outcomes between AirSeal® and standard CO 2 insufflators in patients undergoing the most frequently performed laparoscopic procedures. Methods One hundred and ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Luketina et al 10 . showed in an randomized clinical trial (RCT) that the use of the AirSeal® system in cholecystectomy, colorectal surgery, and hernia repair did not reduce operative time and was associated with higher postoperative shoulder pain compared to standard CO 2 insufflator.…”
Section: Discussionmentioning
confidence: 99%
“…Luketina et al 10 . showed in an randomized clinical trial (RCT) that the use of the AirSeal® system in cholecystectomy, colorectal surgery, and hernia repair did not reduce operative time and was associated with higher postoperative shoulder pain compared to standard CO 2 insufflator.…”
Section: Discussionmentioning
confidence: 99%
“…Because RG is standardized to be performed with ve ports, other means must be considered for minimizing the risk of SE. The valveless insu ation system, AirSeal®, is becoming increasingly popular in robotic surgery because it maintains a stable-pressure pneumoperitoneum and performs continuous smoke evacuation [17,18]. However, the use of this device is also known to increase the risk of SE [15].…”
Section: Discussionmentioning
confidence: 99%
“…The surgical smoke generated by the energy‐based devices in flexible gastrointestinal (GI) endoscopic procedures, such as endoscopic submucosal dissection, obstructs the field of view and usually requires repeated manual suctions and insufflations by endoscopists 3–8 . In contrast, laparoscopic surgery already has systems that can automatically evacuate the smoke in the abdominal cavity, 9–11 and it has already been reported, including ours, that the automatic smoke evacuator provides a better field‐of‐view and further reduces the risk of exposure to harmful compounds, including carcinogenic substances 12–15 . Other reports have shown that surgical smoke contains viruses such as human papillomavirus, and the use of smoke evacuators is recommended for laser surgery 16,17 .…”
Section: Introductionmentioning
confidence: 98%